Methodology analysis of a computational tool used in electronic circuit design - Almeida, Tiago da Silva [UNESP]; Silva, Alexandre C. Rodrigues da [UNESP]; Grout, Ian Andrew (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper considers the importance of using a top-down methodology and suitable CAD tools in the development of electronic circuits. The paper presents an evaluation of the methodology used in a computational tool created to support the synthesis of digital to analog converter models by translating between different tools used in a wide variety of applications. This tool is named MS 2SV and works directly with the following two commercial tools: MATLAB/Simulink and SystemVision. Model translation of an electronic circuit is achieved by translating a mixed-signal block diagram developed in Simulink into a lower level of abstraction in VHDL-AMS and the simulation project support structure in SystemVision. The method validation was performed by analyzing the power spectral of the signal obtained by the discrete Fourier transform of a digital to analog converter simulation model. © 2011 IEEE.
Keywords: computational tool; Digital to Analog Converter; Synthesis; CAD tool; Commercial tools; Computational tools; Digital-to-analog converters; Electronic circuit design; Level of abstraction; MATLAB /simulink; Method validations; Mixed-signal blocks; Model translation; Power spectral; Simulation model; Simulation projects; Simulink; Support structures; Topdown; VHDL-AMS; Computational methods; Computer simulation; Digital integrated circuits; Digital to analog conversion; Discrete Fourier transforms; Electric network analysis; Instruments; Integrated circuit manufacture; Measurement theory; Computer aided design